The hyperparathyroidism-jaw tumour (HPT-JT) syndrome - Bradley, K; Thakker, R (2006)
The hyperparathyroidsim-jaw tumour (HPT-JT) syndrome is an autosomal dominant disorder characterised by the occurence of parathyroid tumours, which may be carcinomas in approximately 15% of patients, and ossifying fibromes, that usually affect the maxilla and/or mandible. More than 15% of HPT-JT patients may also develop renal and uterine abnormalities. The gene causing HPT-JT, referred to as HRPT2, is located on chromosome 1q31.2 and consists of 17 exons that encode a 531 amino-acid protein, designated PARAFIBROMIN. PARAFIBROMIN has been shown to be associated with the human homologue of the yeast Paf1 protein complex which interacts with RNA polymerase II, and as part of this protein complex, PARAFIBROMIN may regulate post-transcriptional events and histone modification. To date 63 HRPT2 mutations have been reported and over 80% of these are nonsense or frameshift mutations that are predicted to result in a functional loss of the PARAFIBROMIN protein because of premature truncation. Moreover, loss of heterozygosity involving chromosome 1q and somatic HRPT2 mutations have been observed in some HPT-JT associated tumours and this is consistent with a tumour suppressor role for HRPT2. HRPT2 somatic mutations also frequently occur in parathyroid carcinomas but not adenomas. In addition, patients with 'non-familial' parathyroid carcinomas may harbour germline HRPT2 mutations. The HRPT2 mutations are scattered throughout the coding region, and there is an absence of a genotype-phenotype correlation. The results of these studies have enabled guidelines for the clinical management and genetic screening for HPT-JT kindreds and patients with parathyroid carcinoma to be proposed.